2014
DOI: 10.1002/cphc.201402673
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Charge Density Evidence for Pnicogen Bonding in a Crystal of Ammonium Chloride

Abstract: Chemical binding in crystalline ammonium chloride, a simple inorganic salt with an unexpectedly complex bonding pattern, was studied by using a topological analysis of electron density function derived from high-resolution X-ray diffraction. Supported by periodic quantum chemical calculations, it provided experimental evidence for weak σ-hole bonds (1.5 kcal mol(-1) ) that involve ammonium cations in a crystal. Our results show this type of supramolecular interaction to be more numerous than has been found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 78 publications
(133 reference statements)
2
17
0
Order By: Relevance
“…Interestingly, the pyramidal N atom in the thermodynamic polymorphic form of acetazolamide does not engage in any form of σ-hole based interaction. Lyssenko et al investigated pnicogen bonding in ammonium chloride (P-43 m) crystal using 120 K high-resolution (sinθ/λ = 1.2 Å −1 ) X-ray diffraction data [79]. They observed four weak σ-hole bonds in tetrahedral ammonium cation (NH4 + ) with Clanion.…”
Section: Carbon Bonding Pnicogen Bonding and Hydrophobic Interactionsmentioning
confidence: 99%
“…Interestingly, the pyramidal N atom in the thermodynamic polymorphic form of acetazolamide does not engage in any form of σ-hole based interaction. Lyssenko et al investigated pnicogen bonding in ammonium chloride (P-43 m) crystal using 120 K high-resolution (sinθ/λ = 1.2 Å −1 ) X-ray diffraction data [79]. They observed four weak σ-hole bonds in tetrahedral ammonium cation (NH4 + ) with Clanion.…”
Section: Carbon Bonding Pnicogen Bonding and Hydrophobic Interactionsmentioning
confidence: 99%
“…The authors furthermore concluded that antimony cages display the best balance between strength and directionality. Recent high‐resolution X‐ray diffraction data by Nelyubina and colleagues provide experimental evidence for a weak σ‐hole in ammonium ions in crystals . Similarly, spectroscopic investigations have been employed to detect and better understand pnictogen bonds …”
Section: Pnictogen Bondingmentioning
confidence: 99%
“…A plethora of theoretical works dealing with PnBs are available in the literature [43,44,[76][77][78][79][80][81][82][83]. However, those presenting experimental evidence are much less common [84][85][86][87][88][89]. Nevertheless, this interaction has been recently proposed for the design and synthesis of supramolecular catalysts by Matile et al [90].…”
Section: Pnictogen Bondingmentioning
confidence: 99%